2012
DOI: 10.1155/2012/281068
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA Damage after Photodynamic Therapy Using a Metallophthalocyanine Photosensitizer

Abstract: Photodynamic therapy (PDT) is a chemotherapeutic approach that utilizes a bifunctional reagent, a photosensitizer (PS) that localizes to the target tissue relative to the surrounding tissue and is toxic when exposed to laser light. PDT rapidly induces cell death, inflammatory and immune reactions, and damage of the microvasculature. DNA damage results from a variety of factors including UV-light, X-rays, ionizing radiation, toxins, chemicals, or reactive oxygen species. The aim of this study was to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…The differences between the effects in the absence and the presence of hOGG1 enzyme after 5 h of PDT exposure showed a significant difference in the level of DNA damage indicating that PDT induced both SB/ALS and oxidized purines. This increased level of DNA damage following PDT exposure is similar to the finding of El-Hussein et al (36) who showed that DNA strand breakage increased significantly in three cancer cell lines in response to PDT. Interestingly, a consistent high background level of SB/ALS and 8-oxoGua was detected in all unexposed and exposed samples before and after light exposure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The differences between the effects in the absence and the presence of hOGG1 enzyme after 5 h of PDT exposure showed a significant difference in the level of DNA damage indicating that PDT induced both SB/ALS and oxidized purines. This increased level of DNA damage following PDT exposure is similar to the finding of El-Hussein et al (36) who showed that DNA strand breakage increased significantly in three cancer cell lines in response to PDT. Interestingly, a consistent high background level of SB/ALS and 8-oxoGua was detected in all unexposed and exposed samples before and after light exposure.…”
Section: Discussionsupporting
confidence: 89%
“…This increased level of DNA damage following PDT exposure is similar to the finding of El‐Hussein et al . who showed that DNA strand breakage increased significantly in three cancer cell lines in response to PDT. Interestingly, a consistent high background level of SB/ALS and 8‐oxoGua was detected in all unexposed and exposed samples before and after light exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Significant success indicated nanomedicine enhancements could benefit Pc4-PDT. ZnPc-PDT: 274 Lung (A549) A comparative study indicated phototoxic responses and cell death Oesophageal (SNO) across all tissue types at differential concentrations despite the Breast (MCF-7)…”
Section: Treatment Of Multiple Cancer Tissue Types/geneticmentioning
confidence: 99%
“…[1][2][3] ROS consistently exhibit antimicrobial and anticancer effects through severe damage to DNA and the cytoplasmic membrane. [3][4][5] It has been reported that aPDT rarely creates drug-resistant bacteria, which is an adverse effect of antibiotic therapy. 6 Since ROS exhibit a broad spectrum of antimicrobial activity, aPDT…”
Section: Introductionmentioning
confidence: 99%